2015
DOI: 10.1186/s12864-015-2044-9
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression profiles of bovine milk exosomes in response to Staphylococcus aureus infection

Abstract: BackgroundMilk exosomes are a rich source of microRNAs (miRNAs) that are protected from degradation. Ingestion of milk and subsequent absorption of miRNAs into recipient cells by endocytosis may play a role in the regulation of neonatal innate and adaptive immunity. In contrast, the miRNA content of milk exosomes may also be indicative of a lactating animal’s health; whereby, the presence or absence of specific miRNAs could serve as biomarkers for early detection of bacterial infection that can lead to mastiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
160
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(172 citation statements)
references
References 75 publications
12
160
0
Order By: Relevance
“…The first study focusing on milk microRNAs was only reported in 2010 (Hata et al., ; Kosaka et al., ) and opened a very new field of research focused on milk microRNAs. From then on, a number of studies have focused on investigating milk microRNAs profiles in various conditions including mammary gland infections (Sun et al., ), breast cancer (Do Canto et al., ; Gu et al., ; Pigati et al., ), lactation periods (Hou et al., ; Na et al., ; Xi et al., ), milk processing (Howard et al., ; Oh et al., ), and digestion (Benmoussa et al., ; Kahn et al., ; Liao, Du, Li, & Lonnerdal, ).…”
Section: Micrornas In Milkmentioning
confidence: 99%
“…The first study focusing on milk microRNAs was only reported in 2010 (Hata et al., ; Kosaka et al., ) and opened a very new field of research focused on milk microRNAs. From then on, a number of studies have focused on investigating milk microRNAs profiles in various conditions including mammary gland infections (Sun et al., ), breast cancer (Do Canto et al., ; Gu et al., ; Pigati et al., ), lactation periods (Hou et al., ; Na et al., ; Xi et al., ), milk processing (Howard et al., ; Oh et al., ), and digestion (Benmoussa et al., ; Kahn et al., ; Liao, Du, Li, & Lonnerdal, ).…”
Section: Micrornas In Milkmentioning
confidence: 99%
“…miRNAs can be secreted out of a cell through extracellular vesicles, via apoptotic bodies, or by being bound to AGO proteins (Turchinovich et al, 2013). In cattle, the presence of circulating miRNAs has been reported in bodily fluids such as milk (Sun et al, 2015), blood, and follicular fluid (Noferesti et al, 2015) and in the in vitro culture media of blastocysts (Kropp et al, 2014; Kropp and Khatib, 2015). miRNAs have shown involvement in a variety of biological processes including organismal development, cell proliferation, cell death, hematopoiesis, and immunity (Wahid et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings suggested that there were new miRNAs in gram-positive Staphylococcus aureus . Of these, partly located in pathogenicity islands of Staphylococcus aureus genome or only existing in pathogenicity bacteria, indicated that miRNAs probably participated in regulating the expression of pathogenic bacteria toxicity (12). RNAIII of Staphylococcus aureus (a type of miRNA) was verified as a toxicity-associated gene, participating the regulation of Staphylococcus aureus pathogenicity (13).…”
Section: Discussionmentioning
confidence: 99%